2000
DOI: 10.1074/jbc.m004685200
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in the Primary Binding Site of Galactose/N-Acetylgalactosamine-specific Lectins

Abstract: The recognition of sugar molecules by carbohydrate-specific proteins, lectins, involves the establishment of an organized set of interactions within the binding site. Hydrogen-bonding interactions are one of the most important factors of molecular recognition in lectinϪsugar interactions, along with van der Waals forces, which, although rather weak (often contributing only a fraction of 1 kcal mol Ϫ1 for each pair of atoms), are frequently numerous and together make a significant contribution to binding (1, 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Similar conclusions were drawn with respect to the structure and specificity of the Maclura pomifera agglutinin (MPA) on the basis of the three-dimensional structure of the lectin complexed with the T-antigen disaccharide Galβ1,3GalNAc [13]. More recently, Swaminathan et al [14] reported that the primary binding sites of jacalin and the galactose-specific winged bean lectin exhibit some plasticity. Indeed, both lectins accommodate the bulky 4-O-methoxy-galactose derivative through a novel C-H…O type of hydrogen bond [14].…”
Section: Introductionsupporting
confidence: 50%
See 2 more Smart Citations
“…Similar conclusions were drawn with respect to the structure and specificity of the Maclura pomifera agglutinin (MPA) on the basis of the three-dimensional structure of the lectin complexed with the T-antigen disaccharide Galβ1,3GalNAc [13]. More recently, Swaminathan et al [14] reported that the primary binding sites of jacalin and the galactose-specific winged bean lectin exhibit some plasticity. Indeed, both lectins accommodate the bulky 4-O-methoxy-galactose derivative through a novel C-H…O type of hydrogen bond [14].…”
Section: Introductionsupporting
confidence: 50%
“…As a result, the binding site of jacalin can accommodate epimeric sugars with differently oriented C-2 and C-4 hydroxyl groups and more or less bulky substituents. The presence of an extended site also accounts for the observed specific binding of Neu5Ac and MurNAc to jacalin and for the recently reported binding of 4-Met-Gal to jacalin [14]. Recently, the occurrence of a rather extended carbohydrate-binding site in KMj, the closely related mannose-specific lectin from A. integrifolia, was reported from thermodynamic and calorimetric studies of the lectin complexed to a trimannoside [35,36].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…41,42 A circulating water-bath was employed to help temperature stabilization. The instrument was allowed to equilibrate overnight at 298 K. Aliquots (5-6 ml) of sugar solution were added from the computer-controlled 250 ml rotating syringe, at 396 rpm into the cell containing 1.36 ml of the lectin solution under isothermal conditions.…”
Section: Isothermal Titration Calorimetrymentioning
confidence: 99%
“…Studies have revealed that the lectin used in our experiments could specifically bind galactose or N-acetyl-dgalactosamine [37]. FITC fluorescence proved to be relatively high on galactosylated PES membranes, while on native PES no fluorescence signal was detected, so the fluorescence images clearly displayed the real immobilization of the galactose derivatives.…”
Section: Discussionmentioning
confidence: 84%